Integrating transcriptome and chemical analyses to reveal the anti-Alzheimer’s disease components in Verbena officinalis Linn - Peng, Shuhuan; Li, Fangyi; Yu, Kuo; Zhou, Fengshu; Yu, Heshui; Liu, Hui; Guo, Jialiang; Li, Guoqiang; Wang, Chunhua; Yan, Xiaohui; Li, Zheng (Frontiers in Plant Science, 2022)
Verbena officinalis Linn. is a kind of traditional Chinese medicine, which has a long history of application and shows good effects on neuroprotection. Therefore, we consider that V. officinalis may be a potential drug for treating Alzheimer's disease (AD). Firstly, ultra performance liquid chromatography-mass spectrometry (UPLC-MS) pointed out that the main chemical components in V. officinalis were iridoid glycosides, phenylethanol glycosides and flavonoids. These compounds were used for molecular docking and the results showed that these compounds had good anti-AD activity. In order to explore the biosynthetic pathway of anti-AD components in V. officinalis, UPLC and ultraviolet (UV) spectrophotometry were used to contents determination and the result was leaf > stem > root. At the same time, 92867 unigenes were annotated in V. officinalis transcriptome. There were 206, 229, 115 related unigenes were respectively annotated in iridoid glycoside, phenylethanolic glycoside, flavonoid pathway, of which 61, 73, 35 were differential expression genes. The components had relatively high expression in leaves, which was consistent with the quantitative results. In addition, the tissue distribution particularity of verbenalin may be related to the branching of pathways. Meanwhile transcription factors VoWRKY6 and VoWRKY7 may be involved in the regulation of iridoid glycoside biosynthesis. Further VoWRKY3, VoWRKY9 and VoWRKY12 may be related to flavonoid biosynthesis. The above research is helpful to explore the biosynthetic pathway of anti-AD components and the regulation mechanism of active components, and to further explore the anti-AD effect of V. officinalis.